Appendage‐restricted gene induction using a heated agarose gel for studying regeneration in metamorphosed Xenopus laevis and Pleurodeles waltl. (16th February 2023) - Matsubara, Haruka; Kawasumi‐Kita, Aiko; Nara, Saki; Yokoyama, Hibiki; Hayashi, Toshinori; Takeuchi, Takashi; Yokoyama, Hitoshi
Abstract: Amphibians and fish often regenerate lost parts of their appendages (tail, limb, and fin) after amputation. Limb regeneration in adult amphibians provides an excellent model for appendage (limb) regeneration through 3D morphogenesis along the proximodistal, dorsoventral, and anteroposterior axes in mammals, because the limb is a homologous organ among amphibians and mammals. However, manipulating gene expression in specific appendages of adult amphibians remains difficult; this in turn hinders elucidation of the molecular mechanisms underlying appendage regeneration. To address this problem, we devised a system for appendage‐specific gene induction using a simplified protocol named the "agarose‐embedded heat shock (AeHS) method" involving the combination of a heat‐shock‐inducible system and insertion of an appendage in a temperature‐controlled agarose gel. Gene expression was then induced specifically and ubiquitously in the regenerating limbs of metamorphosed amphibians, including a frog ( Xenopus laevis ) and newt ( Pleurodeles waltl ). We also induced gene expression in the regenerating tail of a metamorphosed P. waltl newt using the same method. This method can be applied to adult amphibians with large body sizes. Furthermore, this method enables simultaneous induction of gene expression in multiple individuals; further, the data are obtained in a reproducible manner, enabling the analysis of gene functions in limb and tail regeneration. Therefore, this method will facilitate elucidation of the molecular mechanisms underlying appendage regeneration in amphibians, which can support the development of regenerative therapies for organs, such as the limbs and spinal cord. Abstract : We induced appendage‐restricted gene expression by embedding an appendage in a temperature‐controlled agarose gel. We induced gene expression in regenerating limbs and regenerating tails of metamorphosed amphibians ( Xenopus laevis and Pleurodeles waltl ).